Treatment of orbital blowout fracture using a customized rigid carrier. Issue 11 (November 2020) - Osaki, Takeo; Tamura, Ryosuke; Nomura, Tadashi; Hashikawa, Kazunobu; Terashi, Hiroto
Abstract: Purpose: This study aimed to examine the usefulness of treating orbital blowout fracture using a customized rigid carrier. Material and methods: Patients who underwent surgery for orbital blowout fractures in our department from April 2016 to March 2019 were recruited in the study. We molded a rigid thermoplastic material into the same shape as the reconstruction material according to the 3D model and transplanted it into the orbital space along with the reconstruction material. We assessed Hertel exophthalmometry, awareness of diplopia, and the Hess area ratio (HAR%). Results: We performed this procedure in 15 patients with blowout fractures. Reconstruction materials used were iliac bone, absorbable plates, and titanium mesh in 12, 2, and 1 patient, respectively. None of the patients showed a difference of more than 2 mm on Hertel exophthalmometry. Only one patient had diplopia after surgery. The average preoperative and postoperative HAR% were 83.1 and 90.6, respectively. HAR% was more than 85% in 6 of 7 postoperative cases. Conclusions: This method can be applied for surgery using various reconstructive materials and can be a useful method, especially in patients with a wide range of orbital bone defects.